Implementasi Manajemen Bandwidth pada Jaringan WLAN Hotspot Berbasis MikroTik Menggunakan Metode Network Planning and Analysis (NPA) - Taufik Rahman; Moh Faisal Abdullah (Fakultas Teknik Universitas Hamzanwadi, 2026)
This study addresses the importance of stable and equitable internet access in WLAN hotspot networks, particularly in overcoming uncontrolled bandwidth usage that can degrade network service quality. The objective of this research is to implement bandwidth management on a MikroTik-based WLAN hotspot using the Network Planning and Analysis (NPA) method to improve network performance. The NPA method is applied through stages including problem identification, data collection, user needs analysis, network topology design, system implementation, and performance evaluation. The implementation utilizes hotspot features and Simple Queue to allocate bandwidth based on user requirements. Performance evaluation is conducted by comparing Quality of Service (QoS) parameters before and after implementation, including throughput, delay, jitter, and packet loss. The results show a 48% increase in throughput (from 1.25 Mbps to 1.85 Mbps), a 57.14% reduction in delay (from 280 ms to 120 ms), an 83.33% decrease in packet loss (from 6% to 1%), and a 68.42% reduction in jitter (from 95 ms to 30 ms). The main contribution of this study lies in integrating the NPA method with MikroTik-based bandwidth management through a user-based bandwidth planning approach, resulting in a more effective, measurable, and user-oriented network system.